Systematic Literature Review: The Transformation of Principalship: Digital Leadership in Improving Teachers’ ICT Literacy - Fitriani Fitriani (Yayasan Sembilan Pemuda Indonesia, 2026)
In the digital era, educational leadership must evolve beyond traditional management toward a digital leadership paradigm. This study aims to analyze how school principals transform their roles into digital leaders and how this influences teachers’ technology literacy. A systematic literature review (SLR) was conducted, analyzing 15 peer reviewed articles between 2021 and 2026. The findings reveal that effective an inclusive digital leadership style significantly reduces teachers’ resistance to technology while enhancing their digital competencies in both pedagogical and administrative practices. The study’s result Effective and inclusive digital leadership significantly reduces teachers’ resistance to technology while enhancing their digital competencies in both pedagogical and administrative practices. The study’s novelty lies in its focus on the managerial orchestration of cultural change rather than mere hardware provision. It concludes that effective digital transformation depends on the principal’s ability to orchestrate technology-based work culture. The practical implication underscores there is an urgent need for structured digital leadership training for school administrators to sustain educational innovation, particularly in the age of AI. Such training should equip principals with skills to manage cultural transformation, foster teacher buy-in, and integrate technology meaningfully into daily school operations. Contribution study’s this work advances a nuanced understanding of leadership as the pivotal driver of successful technology integration in schools. It concludes that effective digital transformation depends critically on the principal’s ability to orchestrate a technology-infused work culture, thereby providing a conceptual framework for future empirical studies on digital leadership in deep learning and basic education settings.